Fatigue resistance improvement of a forging medium carbon steel using Mischmetal (rare earths) as inclusions (MnS) modifier element. - Jorge Zuno Silva (Nova Scientia, 2016)
For this work, hot-rolled plates of medium carbon steel (0.5%C) were prepared with different sulphur contents (0.023% to 0.065%). Two steels were alloyed with mischmetal (0.01%) as inclusions modifier to evaluate its effect on fatigue and tensile properties. A detailed study of the type, size, shape and distribution of the sulphide inclusions was carried out by optical and SEM microscopy in the as-cast and hot rolled conditions and correlated with their mechanical properties. The mischmetal treated steels developed a globular, small (~2µm) and well distributed MnS inclusions, producing an improvement in tensile strength (840 MPa and 19% elongation) and fatigue behavior (375 MPa), which was not evident on the untreated steels (741 MPa tensile strength and 300 MPa fatigue limit). The fatigue behavior was tested under the E466 standard, by using nine samples per composition in a R.R. Moore – rotating beam fatigue testing machine. The higher fatigue limit was obtained for the mischmetal-treated steel with 0.05%S. These results were discussed and correlated to the small size and globular shape of the MnS inclusions. However, it was observed that, additions of 0.01% of mischmetal are less effective as inclusion modifier when sulphur content is higher than of 0.05%, but it is still good enough to obtain a better fatigue behavior compared with the untreated steel containing 0.023% sulphur.